A social network analysis of the relation between social support and resilience in grandparents raising their grandchildren - Mendoza, Angela Nancy, author; Fruhauf, Christine A., advisor; MacPhee, David, committee member; Coatsworth, Doug, committee member; Portz, Jennifer, committee member (Colorado State University. Libraries, 2018)
The purpose of this study was to use social network analysis (SNA) to examine the relation between social support and resilience in grandparents raising their grandchildren. This was done using an exploratory sequential mixed design. In Study 1, 74 grandparents raising grandchildren completed a survey in which data were collected regarding social support, social isolation, and resilience. Findings aligned with the hypothesis that grandparent caregivers' social support and coping skills were associated with their ability to adapt successfully despite experiencing adversity. Results utilizing Structural Equation Modeling demonstrated direct effects from social support, coping skills, and age to life satisfaction. It was also hypothesized that grandparents who knew other grandparent caregivers would fare better than those who did not know other grandparents raising grandchildren. Findings did not indicate this was the case. In Study 2, SNA was employed to further examine the results from Study 1. This was done by conducting face-to-face interviews with grandparents raising grandchildren from Study 1 which include SNA. Using data from Study 1 participants were placed in one of four resilience quadrants. Sixteen grandparents raising grandchildren were interviewed using social network analysis, five participants from the resilient group, four grandparents from the maladaptive group, five individuals from the competent group, and two participants from the vulnerable group. Analysis of grandparent's ego networks indicated resilient grandparent caregivers' networks were structured in a way that provided more opportunities for the inflow of new information and resources. Resilient grandparents also tended to demonstrate more resourcefulness.